Angiotensin-(1-7) attenuates hypertension and cardiac hypertrophy via modulation of nitric oxide and neurotransmitter levels in the paraventricular nucleus in salt-sensitive hypertensive rats. Issue 16 (26th February 2018) - Liang, Bin; Zhao, Ya-Nan; Wang, Xin; Yu, Xiao-Jing; Li, Ying; Yang, Hui-Yu; Su, Qing; Kang, Yu-Ming; Yang, Zhi-Ming
Abstract : Angiotensin-(1-7) [Ang-(1-7)] is a multifunctional bioactive angiotensin peptide which exerts a cardiovascular protective function mainly by opposing the effects of angiotensin II. Abstract : Angiotensin-(1-7) [Ang-(1-7)] is a multifunctional bioactive angiotensin peptide which exerts a cardiovascular protective function mainly by opposing the effects of angiotensin II. We aimed to determine whether brain Ang-(1-7) regulates nitric oxide (NO) and neurotransmitter levels in the hypothalamic paraventricular nucleus (PVN), and influences sympathetic activity, blood pressure and cardiac hypertrophy in salt-sensitive hypertension. Dahl salt-sensitive rats receiving a high-salt (HS, 8% NaCl) or a normal-salt (NS, 0.3% NaCl) diet were treated with an intracerebroventricular (ICV) infusion of Ang-(1-7) for 6 weeks. Seven rats were measured in each group. In comparison with NS rats, HS rats exhibited significantly increased mean arterial pressure, plasma norepinephrine (NE) and cardiac hypertrophy. In addition, HS rats (compared to NS rats) had increased glutamate, NE and tyrosine hydroxylase (TH) expression, and reduced NO levels as well as reduced expression of γ-aminobutyric acid (GABA) and the 67 kDa isoform of glutamate decarboxylase (GAD67) in the PVN. Treatment with ICV infusion of Ang-(1-7) reversed these changes in the salt-sensitive hypertensive rats. The results suggest that the beneficial effects of brain Ang-(1-7) on salt-sensitive hypertension and cardiac hypertrophy are partly due to an elevation in the NO level and restoration of neurotransmitter balance in the PVN.